NASAL IRRIGATION USING A SALINE SOLUTION TO CLEAN THE NOSE OF ACCUMULATED SECRETIONS AND IRRITANT COMPONENTS - Agis Taufik; Nuriya Nuriya; Galih Noor Alivian (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Introduction: Chronic rhinosinusitis is a disease with a high incidence rate, this disease also has an impact on reducing the productivity and quality of life of sufferers. Rhinosinusitis can be caused by multifactorial causes, but most are also caused by inflammation due to viral infections or allergies, resulting in mucosal edema which results in obstruction of the sinus ostium and impaired drainage of secretions. Purpose: The purpose of this study was to determine the effect of nasal irrigation or nasal washing using saline solution on the symptoms complained of by patients and on the condition of airway clearance from patients, so that it can become additional insight for nurses in caring for patients with rhinosinusitis. Methods: This systematic review was conducted according to the PICO model. Keywords in the search for evidence based research in this literature review include: “nasal irrigation” “rhinosinusitis” A database search was conducted in November 2022 using the Google Scholar, PubMed, Science Direct database. Results and discussion: Based on a review of several journals regarding the implementation of nasal irrigation with saline solution, it was found that nasal irrigation using saline solution had a better effect than standard therapy without nasal irrigation with 0.9% NaCl. In addition, it provides good symptom improvement compared to anti- allergy treatment in patients, improves quality of life, and prevents disease recurrence. Conclusion: Based on the results of 10 journal analyzes that have been conducted by the authors, it can be concluded that nasal irrigation using saline solution is proven to be effective in cleaning the nose of accumulated secretions, crusts, and irritant components, thus improving mucosal cleaning. In addition, nasal irrigation has advantages over other techniques such as nasal sprays.